2005
DOI: 10.1007/s00467-004-1688-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of recombinant human growth hormone in pediatric allograft recipients: a report of the NAPRTCS Transplant Registry

Abstract: Data from the NAPRTCS database were analyzed for growth, allograft function, and targeted adverse events (AE) over a 5-year period in 513 recipients who received recombinant human growth hormone (rhGH) treatment and compared with the outcome of 2,263 concurrent controls who did not receive rhGH. Recipients less than 10 years of age grew better than older recipients. Final adult height was superior in the rhGH-treated group compared with the control group. Allograft function and graft failure rate was similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 30 publications
1
41
0
2
Order By: Relevance
“…Although this study concludes that rhGH induces a persistent increase of growth velocity resulting in normal adult height in the majority of patients, the study mixed patients receiving conservative treatment, dialysis, or renal transplantation, making it difficult to assess the effect of rhGH treatment on growth in RTx patients. In the 2005, in a NAPRTCS report, Fine et al [11] described that rhGH was effective in improving FH in RTx patients. In this study, results of a data base including several centers in the United States were shown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although this study concludes that rhGH induces a persistent increase of growth velocity resulting in normal adult height in the majority of patients, the study mixed patients receiving conservative treatment, dialysis, or renal transplantation, making it difficult to assess the effect of rhGH treatment on growth in RTx patients. In the 2005, in a NAPRTCS report, Fine et al [11] described that rhGH was effective in improving FH in RTx patients. In this study, results of a data base including several centers in the United States were shown.…”
Section: Discussionmentioning
confidence: 98%
“…Studies from the North American Pediatric Renal Transplant Cooperative Study (NAPRTCS) have reported that rhGH treatment is effective in improving growth velocity and final height in pediatric renal allograft recipients [11,12]. In this study, we assessed the efficacy of rhGH treatment in a group of RTx patients and compared it with the spontaneous growth of a RTx group who were not treated with rhGH but who were followed with the same protocol and in the same center.…”
Section: Introductionmentioning
confidence: 98%
“…Only children up to 5 years old exhibited catch-up growth mainly during the first 2 years posttransplantation. In various single-center studies published between 2000 and 2011, the frequency of final height SDS <−2SD varied between 32 % and 77 % [15][16][17][18][19]. Even today, the clinical problem of stunting seems to be greater than is anticipated by the community.…”
Section: Growth Before End-stage Renal Diseasementioning
confidence: 99%
“…Apesar de o tratamento com GH aumentar significativamente a velocidade de crescimento pós-transplante (12), a resposta é menor do que a observada nas crianças em IRC pré-transplante. Fine e Stablein demonstraram altura adulta média de -1,83 ± 0,14 DP nos pacientes transplantados que usaram GH comparado com -2,6 ± 0,05 DP nos que não receberam o tratamento com GH (13). Uma metanálise reforçou os efeitos benéficos do tratamento com GH nas crianças com DRC em diálise ou pós-transplante (14).…”
Section: Tratamento Da Baixa Estaturaunclassified
“…Fine e cols., avaliando 63 crianças transplantadas, não demonstram nenhum caso de rejeição no primeiro ano de tratamento com GH, enquanto no grupo-controle ocorreu três casos de rejeição aguda (20). Não houve aumento na incidência de rejeição ou perda do enxerto quando analisado um grupo maior de pacientes com cinco anos de tratamento com GH (13).…”
Section: Gh Em Doenças Crônicasunclassified